2017
DOI: 10.1016/j.yhbeh.2016.10.016
|View full text |Cite
|
Sign up to set email alerts
|

Sex Steroids Mediate Bidirectional Interactions Between Hosts and Microbes

Abstract: The outcome of microbial infections in mammals, including humans, is affected by the age, sex, and reproductive status of the host suggesting a role for sex steroid hormones. Testosterone, estradiol, and progesterone, signaling through their respective steroid receptors, affect the functioning of immune cells to cause differential susceptibility to parasitic, bacterial, and viral infections. Microbes, including fungi, bacteria, parasites, and viruses, can also use sex steroid hormones and manipulate sex steroi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
67
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(69 citation statements)
references
References 91 publications
(121 reference statements)
1
67
0
1
Order By: Relevance
“…54 The exogenous estrogen and progesterone in IVF treatment are associated with the risk of microbial invasion, because microbes can alter and use host hormones to facilitate growth and survival. 55 In addition, IVF women are exposed to more invasive operations, such as cervical excision procedures, hysteroscopic resection, induced abortion, and the IVF treatment itself, 56 which may be a route for MIAC. 24 In current study, it is hard to untangle the key contributors to the identification of 4 bacterial signals.…”
Section: S Rrna Gene Sequencingmentioning
confidence: 99%
“…54 The exogenous estrogen and progesterone in IVF treatment are associated with the risk of microbial invasion, because microbes can alter and use host hormones to facilitate growth and survival. 55 In addition, IVF women are exposed to more invasive operations, such as cervical excision procedures, hysteroscopic resection, induced abortion, and the IVF treatment itself, 56 which may be a route for MIAC. 24 In current study, it is hard to untangle the key contributors to the identification of 4 bacterial signals.…”
Section: S Rrna Gene Sequencingmentioning
confidence: 99%
“…101 In addition to pathogenic bacteria, commensal bacteria in the gastrointestinal tract are responsive to and can even alter concentrations of sex steroids. 102,103 For example, adoptive transfer of gut commensals from male to female mice increases concentrations of androgens in females and alters the pathogenesis of autoimmune diseases. 102,103 Whether P4-based compounds, including the use of contraceptives alter the composition of the microbiome requires consideration.…”
Section: Infections Of the Gastrointestinal Tractmentioning
confidence: 99%
“…102,103 For example, adoptive transfer of gut commensals from male to female mice increases concentrations of androgens in females and alters the pathogenesis of autoimmune diseases. 102,103 Whether P4-based compounds, including the use of contraceptives alter the composition of the microbiome requires consideration. Based on available data, it can be concluded that progestins protect against gastrointestinal infections by increasing host survival through their immunomodulatory effects.…”
Section: Infections Of the Gastrointestinal Tractmentioning
confidence: 99%
“…Hormonal variations between sexes have a marked impact on antiviral responses (Klein et al 2010; Vom Steeg and Klein 2019). Although influenza titers are largely similar between sexes, experimental influenza infection of male and female mice reveals a greater induction of proinflammatory cytokines and increased morbidity in female mice, whereas males show less production of humoral immune responses (Lorenzo et al 2011;Robinson et al 2011;Klein et al 2012;Vom Steeg and Klein 2017). This differential response to influenza infection is mitigated after gonadectomy, suggesting a role for sex hormones in the pathogenesis of influenza (Robinson et al 2011).…”
Section: Sex Differencesmentioning
confidence: 98%
“…Interactions between hormones and immune mediators in systemic circulation and at the mother-fetal interface alter influenza pathogenesis in the pregnant host, as well as contribute to sex-based differences in the response to infection (Irving et al 2000;Raj et al 2014;van Riel et al 2016;Littauer and Skountzou 2018). Other comorbidities, including stress, depression, body mass index, aging, puberty, and exercise state, contribute to poor infection responses and can compound morbidity in pregnant hosts (Christian et al 2010;Avitsur et al 2011;Soydinc et al 2012;Christian 2014;Ingersoll 2017;Vom Steeg and Klein 2017).…”
Section: Pregnancymentioning
confidence: 99%